Nonlinear Refractive Index of Silicon Nanoparticles: A Short Review - Prusty, Sudakshina (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2014)
This article discusses the nonlinear refractive index of silicon nanoparticles starting from the basic formalism to some of the consequent physical phenomena like self focusing and self phase modulation. Several experimental techniques mainly based on Z-scan are discussed to measure the nonlinear refractive index. Another less explored technique for silicon nanoparticles, which studies the far-field optical fringe pattern formed by spatial self-phase modulation, is also discussed. Computation of the nonlinear refractive index is shown in detail by employing these two techniques. While Z-scan can estimate the nonlinear coefficient of a medium in a chosen time scale, the optical fringe method can predict the overall nonlinear refractive index due to all possible physical mechanisms. Some of the recent results for silicon nanoparticles using these two techniques are also discussed.